2022
DOI: 10.1101/2022.02.06.22270509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding molecular programs in melanoma brain metastases

Abstract: The systemic dissemination of tumor cells and the spatiotemporal development of organ- metastases are associated with loss of therapeutic control and decreased overall survival (OS). The emergence of solitary or multiple brain metastases is frequently observed in melanoma patients and responsible for disease progression and dismal prognosis. Here, we used whole transcriptome and methylome profiling as well as targeted sequencing (TargetSeq) of intraoperative/snap frozen or archived melanoma brain metastases to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 131 publications
(190 reference statements)
0
1
0
Order By: Relevance
“…For example, melanoma cells have been shown to re-instate neural crest-specific transcription factors that may provide an adaptive, survival advantage in the brain microenvironment 16,3739 . Notably, while one recent study has found that AXL and EMT-like melanoma cells are enriched in melanoma brain metastases, another recent study found that brain metastases were instead enriched in neuronal-lineage genes and melanocytic state markers such as MITF and SOX10 40,41 . Most likely, melanoma phenotypic plasticity produces a spectrum of different lineage states that interact cooperatively to maintain tumor survival, persistence, and invasion as they compete for various niches in the brain microenvironment (i.e., perivascular positioning).…”
Section: Discussionmentioning
confidence: 98%
“…For example, melanoma cells have been shown to re-instate neural crest-specific transcription factors that may provide an adaptive, survival advantage in the brain microenvironment 16,3739 . Notably, while one recent study has found that AXL and EMT-like melanoma cells are enriched in melanoma brain metastases, another recent study found that brain metastases were instead enriched in neuronal-lineage genes and melanocytic state markers such as MITF and SOX10 40,41 . Most likely, melanoma phenotypic plasticity produces a spectrum of different lineage states that interact cooperatively to maintain tumor survival, persistence, and invasion as they compete for various niches in the brain microenvironment (i.e., perivascular positioning).…”
Section: Discussionmentioning
confidence: 98%